The students’ writing activities at Yogyakarta private elementary schools - Dinar Martia Azizah (DWIJA CENDEKIA: Jurnal Riset Pedagogik, 2024)
Previous research studies have demonstrated that writing is a hard skill, particularly in the context of English as a Foreign Language (EFL) in Indonesia, yet an essential English language skill that students need to master. In this context, writing activities are expected to be adapted to the characteristics and needs of the students to effectively support the development of this skill. Therefore, the aim of this study is to describe the variety of writing activities for private elementary school students in Yogyakarta. This research is a case study conducted at two private elementary schools in Yogyakarta, both of which share a similar background in achieving numerous accomplishments in the field of English language learning. Data were collected through observation, interviews, and document analysis. Observations were conducted in grades I-IV at both schools. Interviews were conducted with the principal, five English teachers, and eight students. The researcher also analyzed documents including lesson plans, teacher guides, and student textbooks. The results of the study showed that The English teachers of ES A and B provided three forms of assistance to develop children's writing skills namely controlled, guided, and free writing activities. The controlled writing activities are carried out by implementing some techniques, i.e. copying, matching, and dictation. Guided writing activities were conducted using the exercise of filing incomplete blanks, dictation, and media such as invitations and postcards. Free writing activities were carried out through five distinct stages of writing, including finding a topic, holding a brainstorming session, organizing ideas into text, receiving feedback, and revising a draft. Although this study has described the variety of creative writing activities, it has not measured the extent to which these activities improve writing skills. Therefore, future researchers may explore studies that measure the impact of these activities, as well as the development of media and teaching materials, to support the enhancement of students' writing skills.